Evidence of a European seed dispersal crisis - Mendes, Sara Beatriz (2024)
Seed dispersal is crucial for ecosystem persistence, especially in fragmented landscapes, such as those common in Europe. Ongoing defaunation might compromise effective seed dispersal, but the conservation status of pairwise interactions remains unknown. With a literature review, we reconstructed the first European-wide seed dispersal network and evaluated the conservation status of interactions by assessing each interacting partner's IUCN (International Union for Conservation of Nature) conservation status and population trends. We found that a third of the disperser species and interactions face potential extinction and that 30% of the plant species have most of their dispersers threatened or declining. Our study reveals a developing seed dispersal crisis in Europe and highlights large knowledge gaps regarding the dispersers and conservation status of zoochorous plants, urging further scrutiny and action to conserve the seed dispersal service.